Going around in a Circle: A Norwegian Study of Suicidal Experiences in Old Age - Anne Lise Holm (Nursing Research and Practice, 2014)
Depression has repeatedly been found to be a risk factor for completed suicide, particularly when coupled with a pervasive sense of hopelessness. The aim of this study was to evaluate depressed older persons’ suicidal experiences. Data were collected by means of individual in-depth interviews with nine informants living in two districts of Norway. A hermeneutic analysis was performed. One main theme: Going around in a circle and two themes: being alone without meaning in life and struggling to achieve reconciliation emerged from the analysis. An important implication for mental healthcare practice is the need to develop a person’s ability to shape and take control of her/his life. The healthcare organisation must be committed to a plan that sets out strategies enabling suicidal individuals to avoid the negative experience of meaninglessness. It was concluded that suicidal depressed elderly persons need help to escape from their desperate situation. More research is urgently required in order to prevent suicide in depressed elderly persons whose emotional pain is unbearable.